Internal tides and tidal cycles of vertical mixing in western Long Island Sound. Issue 2 (1st February 2016) - McCardell, Grant; O'Donnell, James; Souza, Alejandro J.; Palmer, Matthew R.
Abstract: In estuaries, tidal period variations in the rate of vertical mixing have been observed to result from various causes: in Liverpool Bay and the York River, they have been attributed to tidal straining of the along‐channel density gradient modulating stratification; in the Hudson River they arise from tidal modulation of the height of the tidal current bottom boundary layer (BBL). Along continental shelves, tidal period fluctuations in mixing have been observed to result from the dissipation of internal waves (IWs). Western Long Island Sound (WLIS) moored instrument records indicate that large near‐bottom increases in dissolved oxygen (DO) and heat and a decrease in salt occur during the middle of the flood tide: an analysis of water mass signatures indicates that the transport involved is vertical and not horizontal. Temperature data from a vertical thermistor array deployed in the WLIS for 16 days in August 2009 clearly show a tidal cycle of IW activity creating a mean thermocline depression at midflood of approximately 25% of the water depth with individual IW thermocline depressions of as much as 50% of the water depth. Contemporaneous ADCP measurements show increases in shear due to IWs during the flood. Near‐bottom internal wave activity is maximal at and after midflood and is correlated with near‐bottom temperature and DO tendencies at both tidal and subtidal scales. We conclude that internal tides are an important vertical mixing mechanism in the WLIS through both increased shear from IWs and displacement of the pycnocline into the region of high shear in the BBL. Key Points: Internal waves and tides in Long Island Sound are observed by moored sensors. The occurrence of internal waves relates to near‐bottom scalar tendencies.